Linking ESG Disclosure to Firm Performance and Risk : An International Perspective - Dayal, Smita; Soni, Tarun Kumar; Aggarwal, Ritika; Hotwani, Roshni (Indian Journal of Finance, 2024)
Purpose : The study investigated the relationship between a company’s environmental, social, and governance (ESG) scores, performance, and risk for a cross-country sample across developed and emerging nations. Methodology : The study employed a panel regression approach to assess the impact of a firm’s ESG score on its performance (accounting and market) and risk. The data encompassed 1,973 firms across 17 developed and 14 emerging countries, ranging over 5 regions and 11 industries. Findings : The results revealed a non-linear relationship between ESG scores and business performance, suggesting that ESG activities initially had a negative impact and eventually had positive long-term benefits. Furthermore, the strength of this relationship differed between developed and emerging economies. It indicated regional variances in ESG performance, with Europe and the Middle Eastern countries leading the way. Practical Implications : The study emphasized the importance of considering country, industry, and regional factors while evaluating the impact of the ESG score. Expenditures on ESG activities could have a complex and dynamic influence on company performance, with differences observed across different contexts. Stakeholders need this information to understand how the ESG practices of organizations change over time and how they may affect their financial performance and risk. This may also have financial repercussions for creditors, regulatory bodies, and investors. Originality : To the best of our knowledge, this is the first study to examine the impact of ESG on firm performance and risk at various levels, including country, industry, and region, in both developed and emerging economies.